2016
DOI: 10.1016/j.celrep.2016.11.041
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Origins in Immunoglobulin Switch Regions Regulate Class Switch Recombination in an R-Loop-Dependent Manner

Abstract: Class switch recombination (CSR) at the immunoglobulin heavy chain (IgH) locus generates antibody isotypes. CSR depends on double-strand breaks (DSBs) induced by activation-induced cytidine deaminase (AID). Although DSB formation and repair machineries are active in G1 phase, efficient CSR is dependent on cell proliferation and S phase entry; however, the underlying mechanisms are obscure. Here, we show that efficient CSR requires the replicative helicase, the Mcm complex. Mcm proteins are enriched at IgH swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 77 publications
1
52
0
Order By: Relevance
“…Studies have postulated that such a transcription complex–replication complex collision can lead to DNA double-strand breaks, particularly at fragile sites in the genome [6264]. IgH switch sequences are a special case, as it is here that transcription coupled R loops may be responsible for the formation of origin of replication sites that have a role in synapsis of DNA double-strand breaks [65]. Thus, in many different ways, transcription directionality of RNA polII (including at enhancer sites) at DNA polymerase complex associated sites in the genome may play a role in DNA double-strand break formation and genomic integrity regulation.…”
Section: Properties Of Enhancers That Influence Genomic Integritymentioning
confidence: 99%
“…Studies have postulated that such a transcription complex–replication complex collision can lead to DNA double-strand breaks, particularly at fragile sites in the genome [6264]. IgH switch sequences are a special case, as it is here that transcription coupled R loops may be responsible for the formation of origin of replication sites that have a role in synapsis of DNA double-strand breaks [65]. Thus, in many different ways, transcription directionality of RNA polII (including at enhancer sites) at DNA polymerase complex associated sites in the genome may play a role in DNA double-strand break formation and genomic integrity regulation.…”
Section: Properties Of Enhancers That Influence Genomic Integritymentioning
confidence: 99%
“…Using this approach, studies in the CH12 B cell line did not report any effect on switch region mutation frequency following RNaseH over-expression [42] or via short-term retroviral expression in activated B cells [43,44]. However, whereas one study did not report CSR defects in RNaseH-expressing stable CH12 lines [42], another study reported ~50% decrease in CSR following retroviral infection of RNaseH [43]. Finally, RNaseH over-expression in transgenic mice resulted in a slight increase in mutation on the template strand but did not alter CSR frequency [34].…”
Section: Are R Loops Required For Igh Switch Region Mutagenesis? Pmentioning
confidence: 99%
“…In line with alternative roles for R loops in CSR, a recent study has implicated R loops in promoting the long-range synapsis of donor and acceptor switch regions that is essential for the final, end-joining phase of CSR [43]. Specifically, it was reported that CSR efficiency is dependent on, and correlates with, the activity of origins of replication in switch regions and that R loops contribute to the specification of these origins during early S phase [43].…”
Section: R Loops Influence Csr By Regulating the Dna Replication Lmentioning
confidence: 99%
See 2 more Smart Citations